Teaching Eye Tracking: A Method to Record and Analyse Visual Attention - Brunold, Raphael; Burch, Michael; Vidić, Gabrijela; Zeiter, Jessica (Monografija u povodu 20 godina rada Odjela za informacijske znanosti u Zadru, 2025)
Visual scenes, pictures, interactive user interfaces, or movies and animations are types of visual stimuli that are visually attended to be able to solve certain—simple or complex—tasks. Without tracking the eyes of human observers, it is difficult to analyse in which order and for how long some visual objects are observed to solve such tasks. Many insights from eye movements can be very helpful to understand humans’ visual behaviour with the goal to detect design flaws in the stimuli and to improve them based on visual attention patterns. In this chapter, we describe how the research method of eye tracking can be taught in 10 lectures over a two-week course during a summer school at the University of Zadar. This helps students with nearly no experience in eye tracking to start designing and conducting their own eye tracking studies. They learn how to analyse visual attention data and to evaluate humans’ visual attention behaviour. Our teaching concept consisted of theoretical and practical lecture units while the students worked in an active learning style, i.e., the taught concepts were studied on one’s own desire to reach the teaching goals. Finally, the students described their study design, procedure, technical details, and the visual attention results in a written report. To illustrate the success of our teaching concept, we describe the results of one of several eye tracking experiments, focusing on food menus and which dishes are visually attended, comparing dish description with and without images as an independent variable in the eye tracking study. Finally, we discuss some limitations of eye tracking, particularly focusing on teaching, the eye tracking study itself, and general challenges in this research method.